1993
DOI: 10.3109/00365599309181253
|View full text |Cite
|
Sign up to set email alerts
|

Radical Retropubic Prostatectomy for Localised Prostatic Carcinoma: A Clinical and Pathological Study of 201 Cases

Abstract: To examine the role of radical retropubic prostatectomy in clinically localised prostatic cancer we reviewed a series of 201 patients all of whom had undergone bilateral pelvic lymphadenectomy. Frozen section showed metastatic pelvic lymph nodes in 13 cases and 6 cases were too locally advanced for operation; prostatectomy was done for the remaining 182. The pathological staging was based on examination of sections of the whole organ. In 109 (60%) the carcinoma was confined to the prostate gland or to the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
2
18
1
Order By: Relevance
“…Disorder of voiding was the most distressing problem at 3 months after the operation, which accords with other reports [9,10]. After 1 year the feeling of distress returned to the preoperative level.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Disorder of voiding was the most distressing problem at 3 months after the operation, which accords with other reports [9,10]. After 1 year the feeling of distress returned to the preoperative level.…”
Section: Discussionsupporting
confidence: 90%
“…In the present series the incidence of undesirable sideeffects after radical prostatectomy conformed with other recent reports [10], but postoperative impotence was commoner.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…According to the reports published in recent years, estimated risk of symptomatic VTE ranges from 0.8% to 6.2% in patients, who underwent open prostatectomy, whereas the risk of fatal pulmonary embolism amounts to 0.4-1.1% [190][191][192][193][194][195][196][197][198][199]. Dilioglugi et al found that in the group of 472 patients after prostatectomy, 1.1% suffered from symptomatic pulmonary embolism and 1.3% from DVT [198].…”
Section: Venous Thromboembolism Prophylaxis In Cancer Patientsmentioning
confidence: 99%